Institute of Licensing of Economic Activities in the EU Countries: Lessons for Ukraine - ZELDINA, Olena R.; AVERIANOVA, Yevheniia V. (Journal of Advanced Research in Law and Economics, 2018)
The article examines the licensing systems of economic activity, which are enshrined in the national legislation of such countries of the European Union as Germany, Great Britain and Poland. The authors identify the situation inherent in licensing systems of the above-mentioned EU member states and substantiates the expediency of using these provisions in further reforming of the licensing system of economic activity in Ukraine. The legislation of the European Union aimed at regulating the implementation of certain activities across the whole of the EU, and legislation relating to rules for the mutual recognition of permits and qualifications of specialists in EU member states was analyzed.